Circular economy: The silver bullet for emissions?. (15th December 2022) - Khan, Khalid; Su, Chi Wei; Khurshid, Adnan
Abstract: Sustainable economic development with minimal negative environmental impact is one of the biggest global challenges. The linear system concludes because of rising consumption, production, and economic growth, which makes the system out of resources and results in economic crisis and environmental pollution. The rolling window approach used in the study provides detailed information regarding the relationship between carbon emissions and the circular economy in the Netherlands from 2000:01 to 2020:12. In the full sample causality, the finding reveals the positive influence of the circular economy on carbon emissions. The rolling window explores the causal impact in the sub-sample when there is a time-varying effect. It finds that the circular economy has a negative influence on carbon emissions in certain sub-samples due to a variety of causes. On the other hand, carbon emissions have improved the circular economy's ability to address environmental challenges. Thus, our findings prove the existence of a reciprocal link between the circular economy and carbon emissions. Transitioning to the circular economy setup requires the comprehensive development of models for controlling emissions. The detailed understanding derived from the circular economy will help policymakers to plan the policy for mitigating environmental issues.